Strengthening Eco-Literacy at the Darul Musthofa Islamic Boarding School, Karanganyar, Central Java - Asif Faroqi; Brahmantyo Luqman Sayoko; Galuh Tsani Sanjaya Habib (Nusantara Science and Technology Proceedings, 2023)
The Islamic Boarding School Innovation Real Work Lecture (KKN) is a program where students participating in real work lectures carry out community service at Islamic boarding schools. The situation analysis formulated two main problems at the Darul Musthofa Islamic boarding school related to increasing eco-literacy. Eco-literacy covers various fields, including eco-education, eco-healthy, eco-collaboration, and so on. This boarding school innovation real work lecture program is carried out using several methods, namely: collecting and analyzing potential data as well as problems, ICT and Hydroponics training, as well as socialization on sorting organic and non-organic waste and how to process it. This real work lecture activity produced outputs including community service modules, video works and documentation, mass media publications, and publication of community service journals.